2019
DOI: 10.2319/021019-92.1
|View full text |Cite
|
Sign up to set email alerts
|

Airway and Cephalometric Changes in Adult Orthodontic Patients After Premolar Extractions

Abstract: Objective: To examine changes in the airway and cephalometric measurements associated with orthodontic treatment of adults with and without premolar extractions. The study investigated whether extractions had a direct or indirect effect on the airway and examined selected skeletal and dental features. Materials and Methods: This retrospective study used pre- (T1) and posttreatment (T2) cone-beam computed tomography scans of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
(25 reference statements)
2
19
2
Order By: Relevance
“…Thirty-three articles were then selected for full-text assessment. After the full-text appraisal, 26 articles were excluded due to the following reasons: Article in a different language [30], sample age below 16 years old [24,[31][32][33][34], Different premolar extractions [35,36], Different anchorage designs [25,[37][38][39][40][41][42][43], Different malocclusion [44], Nonretrospective studies [16,19,22,[45][46][47][48][49][50]. Six eligible retrospective study articles were selected in this systematic review [20,22,23,[51][52][53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three articles were then selected for full-text assessment. After the full-text appraisal, 26 articles were excluded due to the following reasons: Article in a different language [30], sample age below 16 years old [24,[31][32][33][34], Different premolar extractions [35,36], Different anchorage designs [25,[37][38][39][40][41][42][43], Different malocclusion [44], Nonretrospective studies [16,19,22,[45][46][47][48][49][50]. Six eligible retrospective study articles were selected in this systematic review [20,22,23,[51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Valiathan et al [24], Pliska et al [26] and Joy et al [37], concluded a negative association between airway space changes and dental extractions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Joy et al [ 30 ] Pliska et al [ 31 ] and Zhang et al [ 32 ], the relationship between extraction of premolars and changes in airway dimensions were noted during orthodontic treatment. They stated that dental extractions affect dental features such as upper and lower incisor position and inclinations and intermolar width.…”
Section: Discussionmentioning
confidence: 99%
“…3 Different aspects were analysed by other authors: effects produced by conventional fixed appliance therapy and/or orthognathic surgery, effects produced by extractive treatments and outcomes generated by functional appliance therapy. [4][5][6][7][8][9][10] Among them, a special interest was devoted to the possible relationships between airway dimensions and different anteroposterior facial patterns. [11][12][13][14][15][16][17][18] The interest in elucidating these relationships is not new: airway and the naso-respiratory function have been in the centre of interest among orthodontists since the seventies.…”
Section: Introductionmentioning
confidence: 99%
“…Back in 2012, Van Vlijmen, based on the then‐available evidence, could claim that only the studies assessing airway diagnostics showed a scientific impact of CBCT in the orthodontic field 3 . Different aspects were analysed by other authors: effects produced by conventional fixed appliance therapy and/or orthognathic surgery, effects produced by extractive treatments and outcomes generated by functional appliance therapy 4‐10 . Among them, a special interest was devoted to the possible relationships between airway dimensions and different anteroposterior facial patterns 11‐18 .…”
Section: Introductionmentioning
confidence: 99%